Analysis of Hydrogen Cyanide Hyperfine Spectral Components towards Star Forming Cores - Loughnane R. M.; Redman M. P.; Keto E. R.; Lo N.; Cunningham M. R. (Open Astronomy, 2011)
Although hydrogen cyanide has become quite a common molecular tracing species for a variety of astrophysical sources, it, however, exhibits dramatic non-LTE behaviour in its hyperfine line structure. Individual hyperfine components can be strongly boosted or suppressed. If these so-called hyperfine line anomalies are present in the HCN rotational spectra towards low or high mass cores, this will affect the interpretation of various physical properties such as the line opacity and excitation temperature in the case of low mass objects and infall velocities in the case of their higher mass counterparts. Anomalous line ratios are present either through the relative strengths of neighboring hyperfine lines or through the varying widths of hyperfine lines belonging to a particular rotational line. This work involves the first observational investigation of these anomalies in two HCN rotational transitions, J=1→0 and J=3→2, towards both low mass starless cores and high mass protostellar objects. The degree of anomaly in these two rotational transitions is considered by computing the ratios of neighboring hyperfine lines in individual spectra. Results indicate some degree of anomaly is present in all cores considered in our survey, the most likely cause being line overlap effects among hyperfine components in higher rotational transitions.